Post-operative pancreatic fistula following splenectomy with or without distal pancreatectomy at cytoreductive surgery in advanced ovarian cancer. Issue 7 (16th June 2020) - Bizzarri, Nicolò; Korompelis, Porfyrios; Ghirardi, Valentina; O'Donnell, Rachel Louise; Rundle, Stuart; Naik, Raj
Abstract : Objective: Splenectomy with or without distal pancreatectomy may be necessary at time of cytoreductive surgery to achieve complete cytoreduction in advanced ovarian cancer. However, these procedures have been associated with peri-operative morbidity. The aims of this study were to determine the incidence of distal pancreatectomy among patients undergoing splenectomy during cytoreductive surgery for advanced ovarian cancer and to determine the incidence, management, treatment, and prognosis of patients with post-operative pancreatic fistula. Methods: Retrospective cohort study of all consecutive patients with FIGO stage IIIC-IVB ovarian, fallopian tube, or primary peritoneal cancer who underwent splenectomy with or without distal pancreatectomy, during primary, interval, or secondary cytoreductive surgery between January 2007 and December 2017. All histologic subtypes were included; patients with borderline ovarian tumor and those undergoing emergency surgery were excluded from analysis. Univariate analyses for survival were generated by Kaplan–Meier survival curves and log-rank (Mantel–Cox) tests for statistical significance. Patients who underwent surgery for recurrence were excluded from survival analysis. Inter-group statistics were performed using Student's t-test for continuous variables, and chi-square test and Fisher's exact test for categorical variables. Results: A total of 156/804 (19.4%) women underwent splenectomy, and of these 22 (14.1%) patients had distal pancreatectomy. Of patients who underwent splenectomy only, 2/134 (1.5%) developed grade B post-operative pancreatic fistula and 6/22 (27.3%) patients who underwent distal pancreatectomy developed grade B and C post-operative pancreatic fistula. Five (83.3%) of six of these patients were symptomatic. Distal pancreatectomy patients had a higher risk of developing post-operative pancreatic fistula when compared with patients who underwent splenectomy only (63.7% vs 9.7%, p=0.0001). Median length of hospital stay was longer in patients with post-operative pancreatic fistula: 16.5 (range 7–38) days compared with 10 (range 7–15) days (p=0.019). There was no progression-free survival (p=0.42) and disease-specific survival (p=0.33) difference between patients undergoing splenectomy with or without distal pancreatectomy. Conclusion: Clinically relevant post-operative pancreatic fistula is a relatively frequent complication (27.3%) following distal pancreatectomy and it is a possible complication after splenectomy only (1.5%).